PERAN KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN KINERJA TIM ADMINISTRATIF DI PUSKESMAS TALISE: STUDI DESKRIPTIF ANALITIK - Nurfianti, Nurfianti; Sanan, Sugiyarso (Ensiklopedia of Journal, 2025)
Abstract: This study aims to analyze the effect of transformational leadership on improving the performance of the administrative team at the Talise Health Center. Transformational leadership styles that include idealized influence, inspirational motivation, intellectual stimulation, and individual attention are studied in the context of administrative performance such as efficiency, timeliness, and accuracy of service. This study uses a descriptive analytical approach with questionnaire and interview instruments. The results of the study are expected to be able to describe the characteristics of transformational leadership at the Talise Health Center, analyze the relationship between the leadership style and the performance of administrative staff, and identify aspects of leadership that have the most positive impact. These findings will contribute both theoretically to the development of leadership science in the primary health sector, and practically through recommendations for improving HR management in the health center environment.Keywords: Transformational Leadership, Administrative Team Performance, Community Health Center, Primary Health Care.